Pengaruh Gaya Kepemimpinan Demokratis Terhadap Kinerja Pegawai Non-PNS di Perpustakaan Wilayah Provinsi Sulawesi Selatan - Muh. Syahdan Zuhair; Muh. Ichwan Musa; Uhud Darmawan Natsir; Khaidir Syahrul (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2023)
This study aims to determine whether there is an influence of the democratic leadership style on the performance of non-PNS employees at the Library Service of South Sulawesi Province. The research method used is a quantitative approach with survey techniques. In this study, data collection was carried out using an online questionnaire with the help of Google form. Respondents in this study were non-PNS employees with a total of 35 people. Data analysis was carried out using Pearson correlation and simple regression with the help of SPSS 25. The results showed that democratic leadership style had a positive and significant effect of 50% on the performance of non-PNS employees at the Library and Archives Service of the Province of South Sulawesi.